Experimental study on the structural behaviors of jacking prestressed concrete cylinder pipe. (March 2018) - Zhang, Yao; Yan, Zhi-guo; Zhu, He-hua; Ju, J. Woody
Highlights: A novel jacking pipe is experimentally investigated under various conditions. Characteristics of crack in different part of pipe are presented. Limit states under combined load are presented. The failure mode of pipe is pointed out. Experimental dataset provides a comprehensive basis for design. Abstract: In this study, full-scale tests were conducted on Jacking Prestressed Concrete Cylinder Pipe (JPCCP) under external load, internal pressure, and combined load in order to evaluate its structural behaviors and possible failure modes. The experimental results indicate that external load plays a critical role in determining the onset of inner concrete core cracking at the invert and crown of a pipe. Once cracking appears in the inner concrete core of JPCCP under external load, the crack propagates rapidly and exhibits significant brittle fracture property. The onset of microcracking first appears in the exterior-reinforced concrete coating at the pipe springline in these three tests. Compared to the inner concrete core, cracks distributed in exterior-reinforced concrete coatings are smaller and narrower, as a result of the restriction imposed by the stirrup. The results of the combined load test show that JPCCP structure transforms from a perfect cycle into a damaged cycle, exhibiting a reduction in section stiffness at the pipe invert as loading increases. When the steel cylinder reaches its yield limit, the prestressing wire at the pipe invert yields soon after, and debonding (delamination) occurs between the steel cylinder and concrete almost simultaneously. Nevertheless, the JPCCP structure features excellent post-cracking capacity after a new equilibrium forms, and it exhibits enhanced ductile properties. Finally, a comparison between test results for JPCCP and Prestressed Concrete Cylinder Pipe (PCCP) is performed to illustrate the failure mode of JPCCP under combined load.